A feasibility study of sentinel lymph node mapping by cervical injection of a tracer in Japanese women with early stage endometrial cancer - Chisa Shimada; Yukiharu Todo; Hiroyuki Yamazaki; Sho Takeshita; Kazuhira Okamoto; Shinichiro Minobe; Katsushige Yamashiro; Hidenori Kato (Elsevier, 2018)
Objective: The aim of this study was to investigate the feasibility of sentinel lymph node mapping characterized by a cervical tracer injection in endometrial cancer. Materials and methods: This retrospective study was carried out using data for 57 patients with endometrial carcinoma who had undergone intraoperative sentinel lymph node mapping and subsequent surgical staging. Technetium colloid and/or indocyanine green was injected into the uterine cervix and a gamma-detecting probe and/or photodynamic eye camera system was used intraoperatively to locate hot spots. Results: Of the 57 patients, 52 (91.2%) had FIGO Stage I disease. Successful unilateral or bilateral mapping occurred in 54 patients (94.7%) and 46 (80.7%), respectively. The median number of sentinel lymph nodes detected was two (range, 0-5). Following sentinel lymph node mapping, 41 patients (71.9%) underwent pelvic lymphadenectomy alone and 16 (28.1%) full lymphadenectomy. The median number of lymph nodes resected was 17 (range, 8-110). Sentinel lymph nodes were involved in four patients (7.0%), two with macrometastases and two with low-volume metastases. The sensitivity and negative predictive value for detecting lymph node metastasis were both 100%. Conclusion: Sentinel lymph node mapping with the use of cervical tracer injection is highly feasible in Japanese women with early stage endometrial cancer. Keywords: Endometrial cancer, Uterine cancer, Sentinel lymph node, Cervical injection, Sensitivity